Unit Cost Analysis for Health Academic and Operational Purposes - Palakawong Na Ayutthaya, Paneevon; Pattanaprateep, Oraluck; Thakkinstian, Ammarin (Ramathibodi Medical Journal, 2020)
Background: Unit cost estimation is one of the key planning tasks of organisation in order to allocate resources to each activity properly. Therefore, this study was conducted applying top-down costing approach, for academic unit cost estimation. Objective: To estimate the unit costs using top-down allocation costing approach for academic and operational purposes of the Department of Clinical Epidemiology and Biostatistics (CEB) at Faculty of Medicine, Ramathibodi Hospital, Mahidol University. Methods: A cross-sectional study of the cost of CEB in fiscal year 2018 was retrieved. Direct and indirect costs were allocated to CEB based on 3 main missions (education, research, and academic services) considering staffs’ activities and time spent for each mission. Three cost per unit of measures (cost per student, cost per publication, and cost per research consultation) were estimated accordingly to these 3 main missions. Results: In the fiscal year 2018, direct and indirect costs were ฿15 178 761 and ฿737 496, respectively. As for staffs’ time spent for each mission activity, CEB mission costs were ฿6 807 282 for education (฿3 914 187 and ฿2 893 095 for MSc and PhD, respectively), ฿5 912 895 for research, and ฿2 186 280 for academic services. Conclusions: Unit cost should be estimated properly to minimise and optimally allocate resources to each activity. This study should be useful for other departments as a guideline for their cost management and resource planning.